2018 AIAA Aerospace Sciences Meeting 2018
DOI: 10.2514/6.2018-0391
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Particle Size on Deposition in an Effusion Cooling Geometry

Abstract: The effect of particle size on particle accumulation within an effusion cooling geometry common to gas turbines was investigated experimentally and computationally.A flat plate with an effusion cooling hole array based on a gas turbine combustor liner was subjected to particulate laden flow in an accelerated deposition facility. The tests were conducted at an engine relevant plate temperature of 1118 K, coolant temperature of 950 K, and held at a constant pressure ratio of 1.03 (cavity to ambient). To elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…One of the challenges facing in film cooling is the deposition of particles, which are mainly originated from the pollutants, e.g., sand, debris, and ash, in inlet air or fuel, on the turbine blade [7][8][9]. These deposits can easily change the surface morphology and block the cooling holes, resulting in the deviation of the film cooling from its original design and thus degrading of the film cooling efficiency and endangering the safety of the turbine blade.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the challenges facing in film cooling is the deposition of particles, which are mainly originated from the pollutants, e.g., sand, debris, and ash, in inlet air or fuel, on the turbine blade [7][8][9]. These deposits can easily change the surface morphology and block the cooling holes, resulting in the deviation of the film cooling from its original design and thus degrading of the film cooling efficiency and endangering the safety of the turbine blade.…”
Section: Introductionmentioning
confidence: 99%
“…Cardwell et al [14] studied the effect of different particle blockages on the mass flow of cooling air under a specific pressure ratio. Wolff et al [9] explored the impact of particle size on the deposition on the film cooling. The results showed that the particle with smaller size was easier to deposit, but the large particle was likely to destroy the deposition.…”
Section: Introductionmentioning
confidence: 99%